New bathymetric record for the fish bighead mora, Laemonema verecundum (Gadiformes: Moridae) in the Gulf of California, Mexico - Morales-Azpeitia, Rufino; López-Martínez, Juana; Valdez-Holguín, José Eduardo (HIDROBIOLÓGICA, 2017)
Background. The presence of Laemonema verecundum (Jordan & Cramer, 1897) had not been previously reported at depths less than 666 m. Goals. The objective of the research was to study the bathymetric distribution of L. verecundum. Methods. In the eastern continental shelf of the Gulf of California, 648 specimens of L. verecundum were collected during two experimental research cruises in September 2004 and February 2005. Results. Specimens were collected at depths between 165 and 483 m, where temperatures ranged between 9.5 and 19.9° C, and average oxygen concentration was 1.7 mg/l. Conclusions. This new record expands the known bathymetric distribution range of this species inhabiting shallow waters in the gulf.